Analysing the optimum number of cupping points for selected diseases by utilising graph colouring - Aziz, Nur Atikah; Yusof, Yuhani; Mohd Radzuan, Hazulin; Wan Sulaiman, Wan Aliaa; Noviantri, Viska (Penerbit Akademia Baru, 2025)
An innovative methodology is proposed in optimizing the cupping points related to stroke, insomnia and back pain diseases through the utilization of a graph colouring method. Personalized treatment strategies and patient management heavily rely on the optimization of cupping points. By leveraging the powerful tools of graph theory and by the application of colouring approach, this study aimed to provide valuable insights into enhancing the optimum number of cupping points for selected diseases. According to the graphical model utilized in this study, this technique also saves time and money because it's imperative to acknowledge that the appliances of two vertices as the most effective nerve point for initial treatment is sufficient and highly efficient. This method is significant from previous methods that required the use of 10 nerve vertices for back pain, 14 for insomnia, and 14 for stroke treatment, thus could have a profound impact on patients' wellbeing, as well as various fields and industries.